Indigenous View of Rural Households to Poverty: The Role of Agro-Ecological Constraints in Kuyu District, Central Ethiopia - Motuma, Feleke Yehuwalashet (Department of Geography Education, University of Jember, 2026)
Before taking any meaningful public action to reduce poverty in Ethiopia’s rural areas, it is necessary to comprehend how rural households see their situation. Hence, the major objective of this study was to look into the indigenous view of rural households and poverty. Through an organized interview schedule, pertinent data were gathered. The collected data were measured using the Rotated Component Matrix, Score Coefficient Matrix, Eigenvalue-One Criterion, Bartlett’s Test of Sphericity, and Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO). Thus, analysis showed that a rural household is considered to be poor when they are with wage workers, have a large number of children, a female head of household, migrate, have little to no grain stock, have poor information-seeking habits, have subpar clothing, subpar fencing, subpar housing, have fewer plough oxen, have fewer livestock, have a low level of education, are unable to transport their members to the health center, have inadequate savings, are not close to all weather roads, do not use extension agents, do not use agricultural inputs, and do not utilize credit service. In conclusion, rural households’ indigenous perspectives on poverty should be acknowledged and valued and that efforts to alleviate poverty should be implemented based on these perceived markers of poverty.